OC-088 IGE sensitisation to food and inhalant allergens in UK adults with EOE: a pilot study. (28th May 2012) - Hayat, J O; Skypala, I J; Till, S J; Kang, J Y
Abstract : Introduction: Food and inhalant allergens have been implicated as triggers of eosinophilic oesophagitis (EoE). Although topical steroid therapy remains the mainstay of treatment in adults, elemental and six food elimination diets have been shown to decrease oesophageal eosinophilia and improve symptoms in children and more recently in adults. Limited data in North American adult EoE patients suggests that food allergens commonly associated with IgE sensitisation are peanut, egg and soy. We hypothesised that IgE sensitisation to foods and/or cross-reactive inhalant allergens plays a role in EoE. To test the hypothesis we designed a pilot study to explore possible relationships between IgE sensitisation to food/inhalant allergens and EoE in a UK adult population. Methods: Ten adult patients with biopsy-proven EoE (>15 eosinophils/HPF) but no previously documented food allergy were included. Participants completed food allergy and dysphagia questionnaires, and underwent skin prick testing (SPT) to a battery of inhalant allergens: timothy grass, birch, six grasses, three trees, plane, mugwort, ragweed, Alternaria, Cladosporium, Aspergillus, house dust mite (HDM) and latex. Foods tested were milk, egg, prawn and cod and plant-derived foods: peanut, hazelnut, sesame, soy, mustard, corn, wheat, barley, celery, raw potato, apple, peach, grape, orange, tomato, melon, kiwi and strawberry. All SPT's were performed in the presence of positive (histamine) and negative (saline) controls. A wheal size 3 mm or more than the negative control was considered positive. Results: Of the 10 subjects (7 m, median age 33 years, range 26–52) who completed the study, eight reported dysphagia to solids nine times or more in the previous month. Two patients had required hospital admission in the previous month. Nine subjects identified one or more specific foods as a trigger for symptoms. The most commonly cited foods that were thought to trigger symptoms were meat (lamb or chicken) in four, nuts in three and citrus fruits or apples in three. Nine subjects had positive skin tests to both grass pollen and HDM; four of these subjects also had positive tests to at least three other inhalant allergens. These four subjects had the highest number of positive skin tests to foods (median of 9).The most common positive food SPTs were barley (7), wheat (5) and potato (4). Conclusion: The high prevalence of IgE sensitisation to foods in this pilot study supports our hypothesis that this plays a role in adult EoE pathophysiology. The high rates of barley and wheat sensitisation raise the possibility of IgE crossreactivity with homologous plant allergens in EoE, notably grass pollen. Further larger studies will be needed to confirm and investigate the significance of these findings. Competing interests: None declared.